PERANAN PONDOK PESANTREN DALAM MENGATASI KENAKALAN REMAJA - Suyono, Suyono (Candi, 2013)
According to the result, it can concluded : (1) Pondok Pesantren Al-Muayyad Surakarta founded in 1930 by KH. Abdul Mannan with KH. Ahmad Shofawi and Prof. KH. Moh Adnan and used the madrasah system data by KH. Ahmad Umar Abdul Manan. With the Madrasah , in this case SMP Al-Muayyad started from the purpose of Pondok Pesantren Al-Muayyad to anticipate the dearth of cadres or the nations that has alhussunah wal jama'ah principles in the future. (2) The daily activities of the student are following the schedule that defined by the committee of the pondok pesantren. They all are required to have discipline about studying , praying, washing and ironing the clothes, etc. All activity in the Pondok Pesantren Al-Muayyad are ?Tarbyah Islamiyah? as the provision for the students to face the challenges in life and society, the kinds and form of the activity are mental and science that can transferred as the provision in the future. (3) In Overcoming the adolescent mischief in Pondok Pesantren Al-Muayyad Surakarta, Student are given Islamic Education as much as possible to practiced by the students in daily life that appropriate with the religious guidance. This is done by the step by step process towards the goal that defined, that is instill the taqwa and akhlaq, and also hold the truth, so can formed the achievers, virtuous that appropriated with the religious guidance. Key words: Boarding School Al-Muayyad Surakarta